WEBLOG FOR TEACHERS AND STUDENTS - Adhi Susilo (Seminar Nasional Informatika (SEMNASIF), 2008)
Educators are always looking for interesting and innovative ways in which to improve the communications skills of their students and in communicating with their students. This is even more important when the students are studying online. Weblogs, originally a simple web browser based system for updating websites, have developed into powerful web based content management systems, capable of acting as a platform for learning that can accelerate the development of expertise learner behaviour. There is a trend to utilize the benefits of the e-learning as a mechanism to improve learning performance of campus-based students. Whilst traditional methods, such as face-to-face lectures, tutorials, and mentoring, remain dominant in the educational sector, universities are investing heavily in learning technologies, to facilitate improvements with respect to the quality of learning. This study explores into the role of weblogs in supporting teachers during their teaching practice and the key factors determining their engagement with weblogs. Underlying our study is an integrative approach that puts weblogs alongside with other popular media in use. An online community was intentionally built with weblogs to facilitate reflection and social interaction among dispersed teachers. In parallel, multiple channels of communication were employed for peer interaction of students. Weblogs were perceived as valuable in relieving isolation, documenting their experience, and expressing their personal feelings. This study sustains our conviction that the integrative approach is vital to have a comprehensive picture of interaction among a community. Our study deepens the insights into the distinct benefit of weblogs as educational media and informs the future development of an online community with weblogs. Weblogs provide a chance for students to experience writing in a public space where their work can have real value both for their classmates and for a wider community. This prepares students for a networked world where communication is essential and often social and where writing can have consequences.